2021
DOI: 10.1186/s12916-021-01994-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of a conditional cash transfer programme on maternal mortality: a nationwide analysis of Brazilian longitudinal data

Abstract: Background Reducing poverty and improving access to health care are two of the most effective actions to decrease maternal mortality, and conditional cash transfer (CCT) programmes act on both. The aim of this study was to evaluate the effects of one of the world’s largest CCT (the Brazilian Bolsa Familia Programme (BFP)) on maternal mortality during a period of 11 years. Methods The study had an ecological longitudinal design and used all 2548 Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 21 publications
3
54
0
Order By: Relevance
“…Higher poverty rates can lead to less access to private structures for physical activity, such as gyms. These findings demonstrate the urgent need for public policies to improve income distribution, giving greater autonomy for individuals to engage in LTPA, as well as enhance other health conditions [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher poverty rates can lead to less access to private structures for physical activity, such as gyms. These findings demonstrate the urgent need for public policies to improve income distribution, giving greater autonomy for individuals to engage in LTPA, as well as enhance other health conditions [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIR, SMR, and SCFR were inversely associated with both the per capita Bolsa Família Programme bene ts distributed in the municipality and the PMR. Several authors have demonstrated the positive impact of Bolsa Família, a cash transfer programme for vulnerable sectors of the Brazilian population, on the decreasing child mortality, 19 the incidence of leprosy in families living in municipalities with a high burden of the disease, 20 and maternal mortality, 21 and increasing the number of people recovering from tuberculosis. 22 In this context, cash transfer programmes for socially vulnerable individuals, such as the Bolsa Família Programme, play a key role in protecting the most basic needs of people, including nutritional security.…”
Section: Discussionmentioning
confidence: 99%
“…The marked increase in leukemia attributable to occupational risk in Latin America in terms of deaths and DALYs can be partially explained by the fact that humans in these countries and regions are mostly engaged in physical labor and have more opportunities to come into contact with toxic substances such as formaldehyde and benzene. Besides, long-term poverty, poor access to healthcare, a lower awareness regarding occupational risk, inadequate prevention measures and screening, and a lower proportion of treatment together make low-income countries more susceptible to leukemia attributable to occupational risk than high-income countries ( 36 38 ). Therefore, in the subsequent campaign to eliminate leukemia attributable to occupational risk, more attention and health resources were warranted in developing countries and low-income regions.…”
Section: Discussionmentioning
confidence: 99%